Integrating Language-Sensitive Pedagogy Across Disciplines: A Qualitative Exploration of Interdisciplinary Practices in Multilingual Education - Makhlouf, Abdelkader; Rabahi, Hanane (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study examines the implementation of language-sensitive pedagogy in the disciplinary contexts of multilingual higher education. Leveraging seminal theoretical frameworks such as the ROAD-MAPPING model (Dafouz & Smit, 2020), translanguaging theory (García & Wei, 2014), and disciplinary literacy (Shanahan & Shanahan, 2008), the article directly attends to long-standing content-area instruction deficits, whereby language often remains an extremely neglected but requisite element in knowledge construction. Using a qualitative synthesis of research evidence, the study examines cross-disciplinary practices, including integrated content and language teaching, co-teaching, language-responsive curriculum design, and professional collaboration between content and language specialists. Outcomes reveal institutional and ideological barriers, such as monolingual norms and inadequate policy support; yet, they also inform transformative approaches that reconceptualize multilingualism as a pedagogical resource. The article argues for structural and ideological reforms in higher education systems through policy-making, curriculum development, and teacher training to promote equity and linguistic inclusion, and suggests an institutional model of reforms based on the integration of disciplinary knowledge and linguistic capability to bridge the divide between language and content. Finally, it calls for a reconceptualization of teaching practice that places language at the center of disciplinary learning, allowing all students, regardless of their linguistic background, to contribute fully and richly to the life of the academy.